Enhancing The Quality Of Service In Mobile Networks Based On Nemo Basic Support Protocol - Alshaibani, Badiea Abdulkarem Mohammed (2018)
To fulfil the need for an uninterrupted Internet access along with the move in mobile networks as an alternative to the end-host mobility, the IETF NEMO working group was created to extend basic end-host mobility support in Mobile IPv6 (MIPv6). This group standardizes NEMO Basic Support Protocol (NEMO BS) to support network mobility. However, the handover latency in NEMO BS is high and the nested tunnels’ problem in the nested NEMO networks is not considered in the main specification of this protocol. Issues affecting the provision of QoS guarantees during the handoff process in NEMO BS are the handover latency, the disruption time, and the handoff failure and the packet loss.